2017
DOI: 10.1590/2359-3997000000269
|View full text |Cite
|
Sign up to set email alerts
|

Circulating omentin-1 might be associated with metabolic health status in different phenotypes of body size

Abstract: This study showed that circulating levels of omentin-1 are useful predictors of metabolic health status in overweight and obese people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Our study results are comparable with several investigations that described lower omentin-1 levels among T2DM. 11 , 12 Literature indicates conflicting results such as a significant positive relationship between serum omentin-1 and BMI and body fat% 13 , a significant negative correlation with BMI, HbA1c, CRP, TC, LDLc, and TG, and notable positive relationship with HDL. 12 A study described no significant link between omentin-1 and lipid profile, FPG, plasma insulin, and hs-CRP 14 , while another research observed its positive association with HbA1c and negative correlation with BMI, waist circumference, glucose, insulin, HOMA-IR, HDL, TG, DBP, and SBP.…”
Section: Discussionmentioning
confidence: 99%
“…Our study results are comparable with several investigations that described lower omentin-1 levels among T2DM. 11 , 12 Literature indicates conflicting results such as a significant positive relationship between serum omentin-1 and BMI and body fat% 13 , a significant negative correlation with BMI, HbA1c, CRP, TC, LDLc, and TG, and notable positive relationship with HDL. 12 A study described no significant link between omentin-1 and lipid profile, FPG, plasma insulin, and hs-CRP 14 , while another research observed its positive association with HbA1c and negative correlation with BMI, waist circumference, glucose, insulin, HOMA-IR, HDL, TG, DBP, and SBP.…”
Section: Discussionmentioning
confidence: 99%
“…Resistin and FGF21 levels tend to be highest in the MUHO population (148, 208). Data on whether omentin levels differ between MHO and MUHO has been inconsistent, with one study suggesting that MUHO subjects have higher omentin levels than MHO subjects (210), and other suggesting the opposite, that omentin levels are negatively correlated with the metabolic syndrome (122, 211). Cytokines such as TNFα and IL-6 as well as the chemokines SAA and MCP-1 have been shown to be elevated in MUHO (208).…”
Section: Metabolically Unhealthy Obesity (Muho)mentioning
confidence: 99%
“…Obesity has become a leading issue globally [ 1 , 2 ] that threatens both psychosocial and physical health, contributing to a higher incidence of many chronic complications, such as nonalcoholic fatty liver disease, diabetes, cardiovascular diseases, cancer, psychosocial disorders, and so on [ 3 – 6 ]. Unlike general obesity, defined as elevated total body adiposity irrespective of its distribution, central obesity represent a high level of abdominal or visceral fat, which is a stronger predictor of obesity-related diseases [ 7 ].…”
Section: Introductionmentioning
confidence: 99%